Evaluation of Toxic Oxidant Activity for Pure Cinnamic Acid in Albino Mice - Nibal, Kh. ,Mousa; Labeeb. Ah. Al-Zubiadi; Ishrak, Ab. Ahmed (Journal of Madenat Alelem University College, 2011)
The study was carried out to determine the toxic, oxidant and antioxidant effects of cinnamic acid in comparison with vitamin C against the mutagenic effect of Cyclophosphamide, which is a chemical compound that damage hepatic cells and has mutagenic effects. The effect was studied in mouse. This invivo system is depended on evaluating the enzymatic activity of two antioxidant enzymes: Catalase and Glutathione Reductase. Two concentrations of pure cinnamic acid 5.6 and 2.8 mg/kg were evaluated to choice the suitable concentration which remembered the negative control. In an interaction experiments, included two types of treatment pre-cyclophosphamide and post–cyclophosphamide was carried out to determine the mechanisms of pure cinnamic acid. Results showed no toxic and oxidant effects in biological system and instead it showed highly performance in preventing or reducing the oxidant stress influences of cyclophosphamide. It increased the Catalase and Glutathione reductase antioxidant activity, especially in dose 2.8 mg/kg. The positive effect was higher when pure cinnamic acid was used as pre-cyclophosphamide treatment and to less extent in post–cyclophosphamide treatment. Therefore, the cinnamic acid can be considered as an antioxidant compound and Desmutagens in the first degree and Bioantimutagens in the second degree.